2020
DOI: 10.1136/bmj.m3502
|View full text |Cite|
|
Sign up to set email alerts
|

Association between the reproductive health of young women and cardiovascular disease in later life: umbrella review

Abstract: Objective To consolidate evidence from systematic reviews and meta-analyses investigating the association between reproductive factors in women of reproductive age and their subsequent risk of cardiovascular disease. Design Umbrella review. Data sources Medline, Embase, and Cochrane databases for systematic reviews and meta-analyses from inception until 31 August 2019. Revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
171
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(206 citation statements)
references
References 153 publications
(280 reference statements)
4
171
0
2
Order By: Relevance
“…Likewise, a prospective study demonstrated that women under 40 years old with premature ovarian insufficiency (POI) showed a 50–70% higher risk of death by ischemic heart disease when compared with those reaching menopause by 50 [ 109 , 110 , 111 ]. In addition, POI seems to predispose to electrocardiographic alterations [ 112 ] with reduced cardiac automaticity [ 108 ].…”
Section: Er Modulation and Mi: Clinical Studiesmentioning
confidence: 99%
“…Likewise, a prospective study demonstrated that women under 40 years old with premature ovarian insufficiency (POI) showed a 50–70% higher risk of death by ischemic heart disease when compared with those reaching menopause by 50 [ 109 , 110 , 111 ]. In addition, POI seems to predispose to electrocardiographic alterations [ 112 ] with reduced cardiac automaticity [ 108 ].…”
Section: Er Modulation and Mi: Clinical Studiesmentioning
confidence: 99%
“…In Canada, as in much of the world, there has been debate concerning: (a) the appropriate timing and method for screening, specifically the utility of a 50 g glucose challenge test (GCT) prior to an oral glucose tolerance test (OGTT) with a higher glucose load (one step vs. two step approach); (b) what constitutes the most appropriate glucose load (e.g., 75 g vs. 100 g in glucose tolerance testing); (c) the specific glucose threshold values above which a test is considered abnormal at different time points following the glucose load; and (d) the number of abnormal values required to warrant a GDM diagnosis [ 3 ]. Although the hyperglycemia observed in GDM typically resolves post-partum, GDM history is a risk factor for incident diabetes mellitus [ 4 ], hypertension [ 5 ], and cardiovascular disease later in life [ 6 ]. The original definitions of GDM were conceived with a focus on the future risk of maternal diabetes mellitus [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…(d) the number of abnormal values required to warrant a GDM diagnosis [3]. Although the hyperglycemia observed in GDM typically resolves post-partum, GDM history is a risk factor for incident diabetes mellitus [4], hypertension [5], and cardiovascular disease later in life [6]. The original definitions of GDM were conceived with a focus on the future risk of maternal diabetes mellitus [7].…”
Section: Introductionmentioning
confidence: 99%
“…Results from studies, examining the association between pregnancy loss, and later myocardial infarction and ischemic stroke have shown ambiguous results, [10,11,14] and meta-analyses have as a result concluded that there is not enough evidence to draw meaningful conclusions about the possible link, although prior stillbirth is increasingly accepted to be a risk factor for later cardiovascular disease. [9,36] To our knowledge, no studies have evaluated the outcome of venous thromboembolism, and further no studies have presented clinically meaningful absolute risk estimates. Adjustment of confounders varied among studies examining the risk of myocardial infarction and stroke after pregnancy loss.…”
Section: Strengths and Weaknesses In Relation To Other Studies Discumentioning
confidence: 99%
“…The reproductive profile is easily assessable and possibly an important indicator for at-risk women. [9] A first step in evaluating the applicability of pregnancy history as a marker for later cardiovascular disease, is large scale investigations into the strength of association. This could facilitate development of new risk stratification schemes and early prevention strategies, such as lifestyle modifications and prophylactic medication, for women not identified by traditional risk factors.…”
Section: Introductionmentioning
confidence: 99%